Principles of circular economy in agrobiotechnology - Korniienko, Iryna; Kermash, Viktoriia; Kuznietsova, Olena; Baranovskyy, Mikhaylo; Yastremska, Larysa (Problems of Environmental Biotechnology, 2024)
An overview of the principles of circular economy in agrobiotechnology is presented